(untitled) (Journal of International Studies, 2019)
Everyone has various perceptions on the importance of planning. It is very common in the society that planning is the approaches used in the centrally planning system in the past or only developing countries have such plans. In fact, all including developed counties have development plans except that they might be referring to them by different terms/names. Development plans helps for country to have clear objectives, directions for all to direct their efforts towards the same objectives. Having a good plan will therefore be helpful in reducing or anticipating future risks. It is also the case that development planning provides certainty and improves the quality of decision-making process for all parts of government – from national, regional to local governments – and for the private sector. There is another important factor that impacts development planning. I am here referring to the importance of effective governance and accountability mechanism when it comes to development planning. Without effective governance, and accountability mechanisms any development agenda will be less successful. Effective governance and accountability mechanism is the bedrock of sustainable development. How we decide on how best to utilize our resources, or what to prioritize with the limited resources or the order in which to implement our priorities is a function of effective governance. Effective governance is therefore part of the necessary infrastructure needed to achieve the goals and objectives contained in any development plan. Effective governance and accountability mechanisms should be legalized, and implementation should enforce for better results. Good plan is only as good as its implementation – and without plan implementation it is just as good as not having a plan at all. Evidence-based monitoring and evaluation is therefore a cornerstone of our development planning and implementation. It is imperative that we continuously track our progress, including identifying unexpected circumstances and problems that might hinder our progress. Монгол Улсын хөгжлийн бодлого төлөвлөлтийн тогтолцооны зарим асуудал Хураангуй: Хүн бүр төлөвлөлтийн ач холбогдлын талаар янз бүрийн ойлголттой байдаг. Төлөвлөлт гэдэг нь төвлөрсөн төлөвлөлтийн системд буюу урьд өмнө зөвхөн хөгжиж буй орнуудад ийм төлөвлөгөөтэй байсан гэх хандлага юм. Үнэндээ бүх хөгжингүй улс орнууд хөгжлийн өөр төлөвлөгөөтэй, өөр өөрөөр нэрлэсээр ирсэн болно. Хөгжлийн төлөвлөгөө нь улс орнуудад хүчин чармайлтаа ижил зорилгод чиглүүлэхэд чиглэсэн тодорхой зорилт, чиглэлтэй болоход тусалдаг. Тиймээс сайн төлөвлөгөөтэй байх нь ирээдүйн эрсдлийг бууруулах эсвэл урьдчилан харахад тустай болно. Хөгжлийн төлөвлөлт нь үндэсний, бүс нутгийн, орон нутгийн засаг захиргаанаас эхлээд хувийн хэвшлийн бүхий л хэсэгт шийдвэр гаргах үйл явцын чанарыг сайжруулж байгаа явдал юм. Хөгжлийг төлөвлөхөд нөлөөлдөг бас нэг чухал хүчин зүйл бол үр дүнтэй засаглал, хариуцлагын механизм юм. Үр дүнтэй засаглал, хариуцлагын механизм бол хөгжлийн аливаа хөтөлбөр амжилттай хэрэгжих үндсэн нөхцөл, мөн түүнчлэн тогтвортой хөгжлийн үндэс болдог. Түлхүүр үг: Монгол Улс, Хөгжлийн бодлогын төлөвлөлтийн тухай хууль, Монгол Улсын Тогтвортой хөгжлийн үзэл баримтлал 2030, төлөвлөлтийн тогтолцоо, зарчим